PELATIHAN PEMBUTAN CAIRAN DISINFEKTAN STANDAR WORLD HEALTH ORGANIZATION (WHO) DALAM PENANGGUNALANGAN PERSEBARAN PANDEMIK CORONAVIRUS (COVID-19) DI DESA ALUE SENTANG KECAMATAN TUALANG CUT KABUPATEN ACEH TAMIANG - Kartika Aprilia Putri; Fitriani Fitriani; Fadhliani Fadhliani (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
Coronavirus (Covid-19) cases continue to show an increase in Indonesia. To prevent the spread of coronavirus, especially in Alue Sentang Village, it is necessary to break the chain of virus spread. One way is by spraying desinfectants. Due to the large use of desinfectants in the community, it is necessary to empower the community, especially in training and assistance in making disinfectant fluids with WHO standards. Compounds used as desinfectants include distilled white vinegar, hydrogen peroxide, chlorine, etc. The method used in this activity was the direct approach method, practice, and lectures. The approach method was carried out by listing the problems faced by partners regarding Covid-19. The lecture method was carried out by providing information to partners about the advantages and benefits of using WHO standard disinfectants in inhibiting the activity of microorganisms (bacteria, fungi, parasites, and viruses). The practical method was carried out by providing training and assistance in making WHO standard disinfectant fluids